Poverty Alleviation and Child Labor - Edmonds, Eric V.; Schady, Norbert (World Bank, Washington, DC, 2012)
Does child labor decrease as household income rises? This question has important implications for the design of policy on child labor. This paper focuses on a program of unconditional cash transfers in Ecuador. It argues that the effect of a small increase in household income on child labor should be concentrated among children most vulnerable to transitioning from schooling to work. The paper finds support for this hypothesis. Cash transfers have small effects on child time allocation at peak school attendance ages and among children already out of school at baseline, but have large impacts at ages and in groups most likely to leave school and start work. Additional income is associated with a decline in paid work that takes place away from the child's home. Declines in work for pay are associated with increases in school enrollment, especially for girls. Increases in schooling are matched by an increase in education expenditures that appears to absorb most of the cash transfer. However, total household expenditures do not increase with the transfer and appear to fall in households most impacted by the transfer because of the decline in child labor.